2020
DOI: 10.19177/rgsa.v9e42020297-315
|View full text |Cite
|
Sign up to set email alerts
|

Descarga Sólida Do Rio Itajaí Do Sul Mediante Aplicação Do Método Simplificado De Colby

Abstract: O monitoramento hidrossedimentológico é uma ferramenta importante na supervisão a ser realizada em uma bacia hidrográfica, visto que os corpos hídricos são utilizados nos mais variados fins, como abastecimento público, navegação, irrigação, entre outros. Como a sub-bacia do Itajaí do Sul não apresenta este acompanhamento, buscou-se neste trabalho mediante utilização de uma ferramenta computacional, estimar a descarga sólida total diária da sub-bacia em um período de dois anos. Ainda, como item complementar, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…Studies show high correlation between turbidity and the values for suspended sediment concentration, generally used to measure the effects of erosion in river environments (Merten et al, 2014;Ferraz et al, 2018;Baucke et al, 2020). In the present study, the data for soil loss obtained in the laboratory showed a -95.91% correlation with the signal obtained from the turbidity sensor.…”
Section: Resultssupporting
confidence: 59%
“…Studies show high correlation between turbidity and the values for suspended sediment concentration, generally used to measure the effects of erosion in river environments (Merten et al, 2014;Ferraz et al, 2018;Baucke et al, 2020). In the present study, the data for soil loss obtained in the laboratory showed a -95.91% correlation with the signal obtained from the turbidity sensor.…”
Section: Resultssupporting
confidence: 59%